Use of Particle Agglutination Assay in the Diagnosis of Japanese Encephalitis and Dengue - Pandey, Basu Dev; Pun, Ramesh; Pant, Krishna Prasad (Nepal Journal of Science and Technology, 2011)
Japanese encephalitis (JE) and dengue are vector borne viral diseases that are endemic in the territory of Nepal. The purpose of the study was to assess the disease burden and to compare the results between particle agglutination and enzyme linked immunosorbent assay. A total of 185 serum samples of suspected Japanese encephalitis (JE) viral fever, dengue fever, malaria and typhoid were collected in the year 2005 (August-October) and 2006 (August- November) from hospitals of Bardiya, Banke, Dang, Kathmandu and Parsa. The samples were investigated by particle agglutination and enzyme immunoassay at Everest International Clinic and Research Centre, Kathmandu. Out of 141 samples from suspected diseased patients, 51% had a positive Japanese encephalitis virus (JEV) specific immunoglobulin M by particle agglutination assay while the anti-dengue immunoglobulin M positivity rate was 22.7% among 44 samples by the same assay. The specificity of particle agglutination kit against Japanese encephalitis and dengue was high as evident from absence of cross reactivity with other diseases like malaria, typhoid, kala-azar and leptospira. Thus, particle agglutination assay can be used as a tool for diagnosis of the diseases in developing countries like Nepal. Key words: dengue virus; endemic; Japanese encephalitis; particle agglutination DOI: 10.3126/njst.v11i0.4144 Nepal Journal of Science and Technology 11 (2010) 189-192